2007
DOI: 10.1016/j.postharvbio.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of steamer jet-injection as alternative to chlorine in fresh-cut lettuce

Abstract: Short-time steam processing was used as an alternative to chlorine (100 mg L−1 ) in sanitising fresh-cut lettuce. Quality (pH, water content, colour, potential browning, browning-related enzymes and texture), safety (mesophilic counts) and antioxidant markers (ascorbic and carotenoids) were monitored in lettuce stored for 10 days at 4 • C. The steam treatment produced a shocking effect on lettuce metabolism, showing a significant (p < 0.05) reduction in respiration (from day 3 to 7) and a partial inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…Disinfection processes incorporating chlorine are often applied to fresh vegetables to enhance safety and shelf-life profiles, but its use has limitations and disadvantages, such as a reduced antimicrobial effectiveness or the possible formation of carcinogenic chlorinated compounds (Li, Brackett, Shewfelt, & Beuchat, 2001;Martín-Diana et al, 2007). With increased concern about efficacy and toxicological safety of chemicals and synthetic preservatives, the demand for natural alternatives has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Disinfection processes incorporating chlorine are often applied to fresh vegetables to enhance safety and shelf-life profiles, but its use has limitations and disadvantages, such as a reduced antimicrobial effectiveness or the possible formation of carcinogenic chlorinated compounds (Li, Brackett, Shewfelt, & Beuchat, 2001;Martín-Diana et al, 2007). With increased concern about efficacy and toxicological safety of chemicals and synthetic preservatives, the demand for natural alternatives has increased.…”
Section: Introductionmentioning
confidence: 99%
“…With minimally processed lettuce, Martin‐Diana and others (2007) verified the effect of steamer jet‐injection as an alternative to the usual chlorine sanitizing treatment. Significant reduction of ascorbic acid content and, to a lesser extent, of the total carotenoid concentration during storage for 10 d at 4 °C was observed.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, sanitizers with oxidizing ability are expected to exhibit stronger decolorizing effects than organic acids. In a study by Martín-Diana, Rico, Barry-Ryan, Frías, Henehan, and Barat (2007), the -a * values of fresh-cut lettuce were found to be decreased after treatment with 120 ppm chlorine for 1 min. Bermúdez-Aguirre and Barbosa-Cánovas (2013) found that L * and WI values increased after exposure to 15 ppm ozone, whereas 0.5–1.5% CA did not interfere with the visual quality of the produce.…”
Section: Resultsmentioning
confidence: 96%